(untitled) - Carlton-LaNey, Iris B; Carlton-LaNey, Iris B (Washington, DC, 1999)
Papers originally presented at the 23rd Annual National Institute on Social Work and Human Services in Rural Areas held in 1998 at the University of North Carolina.; Includes bibliographical references and index.; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social service, Rural -- United States -- Congresses; Human services -- United States -- Congresses; Dịch vụ xã hội -- Nông thôn -- Hội nghị -- Mỹ (Hoa Kỳ); Dịch vụ con người -- Hội nghị -- Mỹ (Hoa Kỳ)